Tugas-Tugas Pertumbuhan dan Perkembangan Peserta Didik Usia 12-15 Tahun (SMP) - Winanda, Ika Adma; Mahardika, I Ketut; Suci, Shinta Dewi; Rofiqoh, Vivi Fadilatul (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to determine the growth and development tasks of students aged 12-15 years. This research uses a literature view which is carried out by looking at several pieces of literature from other articles. The results obtained in this article are the development and growth tasks of students aged 12-15 years including: Physical Development, Intelligence Development, Emotional Development, Social Development, Moral Development, Personality Development and Religious Development. Where development is a progressive change that discovers the way organisms behave and interact with the environment as well as increasing the structure and function of the body which is more complex in the ability of gross movement, fine movement, speech and language as well as socialization and independence. Human growth is a physical change to become bigger and longer, where the process occurs from the time the child is born until this development and growth can occur in adolescence.